1992
DOI: 10.1002/ps.2780340209
|View full text |Cite
|
Sign up to set email alerts
|

Comparative measurements of resistance to insecticides in three closely‐related old and new world bollworm species

Abstract: Toxicity measurements were made with three closely‐related Bollworm species, Heliothis virescens F., Helicoverpa zea (Boddie), and Helicoverpa armigera (Huebner) using insecticides of 3 different chemical classes. Tests were carried out by a leaf‐dip method using neonate larval stages, a topical application test on 3rd larvae, and a topical test with imagines. H. armigera populations from Ivory Coast, Turkey, Thailand, and India were obtained and investigated. H. virescens originated from the USA and Colombia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 7 publications
2
9
0
Order By: Relevance
“…Similar report was followed by Ernst & Dittrich [13]. Then, resistance to lambda-cyhalothrin and esfenvalerate were reported in the Adana and Antalya strains of H. armigera [8].…”
Section: Introductionsupporting
confidence: 73%
“…Similar report was followed by Ernst & Dittrich [13]. Then, resistance to lambda-cyhalothrin and esfenvalerate were reported in the Adana and Antalya strains of H. armigera [8].…”
Section: Introductionsupporting
confidence: 73%
“…Pyrethroids became available for use in cotton in the late 1970s and early 1980s and were very extensively used, to the exclusion of other products. Very substantial resistance to cypermethrin in the tobacco budworm was noted from 1985 and has been documented by Ernst & Dittrich (1992) and con¢rmed by McCa¡ery (1994).…”
Section: (Iii) Heliothis Virescens In Colombiamentioning
confidence: 80%
“…These pyrethroids were always mixed or rotated with organophosphate insecticides in an e¡ort to prevent or delay resistance in bollworms (Alaux et al 1997). Ernst & Dittrich (1992), in a comparative survey of resistance in heliothines around the world, could ¢nd no evidence for resistance to pyrethroids in the Ivory Coast. Vassal et al (1997) con¢rmed that before 1992 there was no change in resistance to pyrethroids but in subsequent years susceptibility decreased and by 1995 and 1996 signi¢cant resistance was recorded.…”
Section: (Xiii) Helicoverpa Armigera In Africamentioning
confidence: 98%
See 1 more Smart Citation
“…Observation of cross‐resistance patterns in Pakistani field populations of H. armigera showed that alpha‐cypermethrin was more highly resisted than zeta‐cypermethrin 41. Similarly, in field strains of H. virescens from Colombia and Helicoverpa zea (Boddie) from Guatemala and Nicaragua, ‘high‐ cis ’ cypermethrin (80/20 ratio of cis/trans isomers) was more highly resisted, with factors of 90‐, 134‐ and 49‐fold respectively, than ‘normal’ cypermethrin (40/60 ratio of cis/trans isomers) which was resisted with factors of 45‐, 53‐ and 14‐fold respectively 42. A detailed investigation of the biological activity of cyfluthrin isomers in resistant strains of P. xylostella and H. virescens provides further support for higher resistance to cis isomers and lower resistance to trans isomers 43.…”
Section: Discussionmentioning
confidence: 99%